Efficacy and tolerability of interferon alpha treatment in patients with chronic cystoid macular oedema due to non-infectious uveitis. Issue 7 (24th March 2009) - Deuter, C M E; Kötter, I; Günaydin, I; Stübiger, N; Doycheva, D G; Zierhut, M
Abstract : Aim: To assess the efficacy and tolerability of interferon (IFN) alpha in chronic cystoid macular oedema (CMO) due to non-infectious uveitis. Methods: Retrospective analysis of an interventional case series. IFN alpha-2a was administered at an initial dose of 3 or 6 million IU per day subcutaneously and tapered afterwards to the lowest possible dose to maintain the absence of CMO. Treatment efficacy was assessed by optical coherence tomography. Results: Twenty-four patients with chronic CMO (median duration 36.0 months) due to non-infectious anterior (n = 2), intermediate (n = 18) or posterior (n = 4) uveitis have been analysed. Ineffective pretreatment included systemic corticosteroids (all patients), acetazolamide (22 patients) and at least one immunosuppressive drug (18 patients). IFN therapy was shown to be effective ( = complete resolution of CMO within 3 months, able to taper IFN) in 15 patients (62.5%), partly effective ( = incomplete resolution of CMO, unable to taper IFN) in six patients (25.0%) and not effective ( = no response or recurrence of CMO) in three patients (12.5%). IFN treatment was generally well tolerated. Common side effects including flu-like symptoms, fatigue or increased liver enzymes were dose-dependent and led to discontinuation of IFN in only one patient. Conclusion: The data demonstrate IFN alpha to be an effective and well-tolerated therapy for chronic refractory uveitic CMO.